Pengaruh Variasi Latihan Ladder Drill Terhadap Kelincahan Pemain Ekstrakurikuler Futsal SMA Negeri 6 Malang: The Effect of Ladder Drill Training Variations on the Agility of Futsal Extracurricular Players at SMA Negeri 6 Malang - Dhoni Arga Hasibuan; Sapto Adi; Nanang Tri Wahyudi; Slamet Raharjo (CV. Nusantara Sporta, 2023)
The aim of this research is to find out the effect of providing variations of ladder drill training on the agility of futsal players. Considering the characteristics of the fast and dynamic game of futsal, futsal athletes need good agility components. This research uses a pre-experimental method using a one group pretest-posttest design. This research lasted for six weeks with meetings three times a week. There are 10 variations of exercise movements that will be used with the stipulation that once a week 5 different movement variations will be selected. The population studied was futsal extracurricular players at Senior High School 6 Malang using a purposive sampling technique for sampling so that 15 samples were selected that met the research criteria. The instrument used was the Illinois Agility Test. The data analysis technique in this research uses paired sample t-test. The t-test results show that the paired sample t-test analysis of the agility test shows a significance value of 0.000 which is smaller than the significance level of 0.05. This shows that H1 is accepted and H0 is rejected. Therefore, it can be concluded that variations in ladder drill training have a significant impact on player agility